2011
DOI: 10.1016/j.pnpbp.2010.09.017
|View full text |Cite
|
Sign up to set email alerts
|

The neuroendocrinology of primate maternal behavior

Abstract: In nonhuman primates and humans, similar to other mammals, hormones are not strictly necessary for the expression of maternal behavior, but nevertheless influence variation in maternal responsiveness and parental behavior both within and between individuals. A growing number of correlational and experimental studies have indicated that high circulating estrogen concentrations during pregnancy increase maternal motivation and responsiveness to infant stimuli, while effects of prepartum or postpartum estrogens a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
112
0
2

Year Published

2011
2011
2017
2017

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 118 publications
(121 citation statements)
references
References 151 publications
0
112
0
2
Order By: Relevance
“…Thus, chronic peripartum stress can affect both the basal hypercorticism, as well as the attenuated stress responsivity observed in lactation. Together with the findings from human studies, the animal data suggests that an optimal corticosterone/cortisol window exists, in which an elevation above nulliparous/virgin levels is beneficial while the higher levels observed after stress exposure negatively affect maternal care [see also [179] for more details]. Consequently, it is suggested that such stress-induced prevention of these peripartum-associated neuroendocrine adaptations may underlie postpartum mood disorders [1,4,5].…”
Section: Consequences Of Chronic Stress In Pregnancy On Physiology Nmentioning
confidence: 99%
“…Thus, chronic peripartum stress can affect both the basal hypercorticism, as well as the attenuated stress responsivity observed in lactation. Together with the findings from human studies, the animal data suggests that an optimal corticosterone/cortisol window exists, in which an elevation above nulliparous/virgin levels is beneficial while the higher levels observed after stress exposure negatively affect maternal care [see also [179] for more details]. Consequently, it is suggested that such stress-induced prevention of these peripartum-associated neuroendocrine adaptations may underlie postpartum mood disorders [1,4,5].…”
Section: Consequences Of Chronic Stress In Pregnancy On Physiology Nmentioning
confidence: 99%
“…There is also considerable evidence that these influences are important for the development of normal parent-infant relationships, although they have been suggested to be more relevant to the establishment of maternal than paternal care (72). Conversely, a recent longitudinal study of plasma OT levels among new parents with their first infant found there were increasing plasma OT levels over the first 6 months regardless of parental gender (13).…”
Section: Neuropeptide-dopaminergic Interactionsmentioning
confidence: 99%
“…The hormones mentioned above are also involved in maternal care-taking behaviors and motivation: Sex steroids positively affect maternal responsiveness during late pregnancy in marmosets and tamarins . Likewise, pre-partum estrogen levels are positively linked to subsequent maternal care-taking behavior in tamarins (Pryce et al, 1988), macaques (Bardi et al, 2003), and humans (Fleming et al, 1987; see also Maestripieri, 2001a, 2001b, and Saltzman and Maestripieri, 2011). Conflicting results were described for common marmosets (Pryce et al, 1995), black-tufted marmosets (Fite and French, 2000), gorillas (Bahr et al, 2001), and baboons (Bardi et al, 2004; see also Maestripieri, 2001a;Saltzman and Maestripieri, 2011).…”
mentioning
confidence: 99%
“…Primate maternal behavior can also be influenced by stress-related hormones and neuropeptides (Saltzman and Maestripieri, 2011), whereas there is no indication for a positive link of prolactin and maternal care based on the limited available evidence in marmosets (Saltzman and Abbott, 2005). OT seems to be fundamentally involved in motivational priming during mother-infant bonding in mammals (Carter, 1998;Maestripieri, 2001b) and it is positively involved in maternal behavior in rats (Fahrbach et al, 1984;Pedersen et al, 1994) and sheep (Kendrick et al, 1987), but such effects have not been studied in primates yet.…”
mentioning
confidence: 99%